Non-destructive method for maturity assessment of Indonesian’s mangoes by NIRS spectroscopy - Muhammad Ikhsan Sulaiman; Agus Arip Munawar; . Ichwana (Syiah Kuala University, 2012)
Rapid and non-destructive method to determine maturity quality of mangoes accurately has played an increasing role in the fruits supply chain involving automation. Diffuse reflectance spectra (R) and absorbance spectra (Log 1/R) in the spectral range from 900 to 1400 nm were measured using NIRS spectroscopy at three different points of 257 Indonesians mangoes cultivar arumanis, manalagi, gadong, gincu and golek of different ripeness indices. Through principle component analysis (PCA) and cluster analysis (CA) of the absorbance and reflectance spectra, cultivars can be differed with an accuracy of 99.8%. Multiple linear regression was applied to develop calibration models from mangoes with soluble solid content ranged between 5.5 and 13.5 % Brix and firmness ranged between 0.25 and 4.50 kgf. Log 1 /R calibration model could assess the soluble solid content and firmness of the mangoes with higher accuracy than R model with the coefficient of determination of 0.96 and 0.93, respectively. Results showed that NIRS spectroscopy has the feasibility to be employed in the maturity measures of Indonesian’s mangoes.